도시슬로건이 도시기억의 인출에 미치는 부정적 영향 :슬로건과 관련 없는 도시기억을 중심으로 - 김도형(Dohyung Kim); 황인석(Insuk Hwang) (한국콘텐츠학회 논문지, 22(2), 2022)
This study tests the hypotheses that city slogan reduces the retrieval of city memory unrelated to the slogan from the long term memory and that some variables moderate this effect, using the experimental method. The theoretical basis for the hypotheses is from the structure of the long term memory and the principle of memory retrieval discussed in ANM(Associative Network Model). For the test of hypotheses, the study adopted 4 experimental groups (2(slogan relevance: high or low) * 2(slogan concreteness: high or low)) and 1 control group. Each experimental group was exposed to one slogan corresponding to its condition while the control group was not. Then, the recall score was compared among experimental and control groups. One hundred and seventy-four undergraduate students belonging to the college of the authors participated in the study. The sample group was between 18 and 27 years of age, with an average of 22.4 years, and 54 percent comprised males. Results showed that city slogan had a negative effect on the retrieval of city memory unrelated to the slogan in most experimental conditions. This effect was more evident when the slogan had high relevance or high concreteness. But the main effect did not appear when the slogan had low relevance and low concreteness. 본 연구는 도시슬로건의 사용이 경우에 따라서는 도시 관련 기억의 인출에 부정적 영향을 미칠 수 있음을 전제로 관련 변수의 효과를 실험적으로 고찰하고 있다. 가설 검정을 위해 본 연구는 4 실험집단(2(슬로건의 도시 관련성: 고 혹은 저) × 2(슬로건의 구체성: 고 혹은 저)과 1개의 통제집단을 구성하였다. 실험집단은 각 조건에 맞은 도시슬로건에 도출되었으며, 통제집단은 도시슬로건에 노출되지 않았다. 이후 각 집단의 기억인출 점수를 비교하게 된다. 표본은 대학 학부생 174명으로 구성되었으며, 남자 54%, 연령 분포 만 18-27세, 연령 평균 만 22.4세이다. 연구결과 도시슬로건은 슬로건과 관련 없는 도시기억의 인출을 방해하는 경우가 많은 것으로 나타났다. 이러한 방해효과는 슬로건이 도시와 관련성이 높을수록, 구체적일수록 더 커지는 것으로 나타났다. 그러나 도시 관련성이 낮고 구체성이 낮은 슬로건에서는 방해효과가 발견되지 않았다. 본 연구는 기존 연구와 달리 도시슬로건의 부정적 효과를 다루고 있다는 차별성을 가질 뿐만 아니라 실무적으로도 관련 담당자들에게 도시슬로건의 제정과 관련된 전략적 시사점을 제공하고 있다.